Comparison between different dose regimens of misoprostol in termination of early pregnancy - Majeed, Fatehiya; Al-Ani, Hanaa; salih jasim, Sarab (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objective: compares efficacy & side effects of vaginal put of 400 or 600 microgram of cytotic in repeated doses in termination of first trimester gestational age. Desgn: Randomized prospect study. Setting and duration of study: Maternity teaching hospital in Sulaimani from 1st of January to the end of June 2009. Patients and methods: This study was included 90 pregnant women admitted during first trimester of gestation, requiring termination of pregnancy because of fetal demise. These patient are divided into two groups: (45) women received 600 mcg of misoprostol vaginally and other group 45 were received 400 mcg of it also vaginally. Misoprostol was given every 6hr for three doses. They were observed and evaluated in 24 hours.Result: Group1 had a complete abortion rate of 35.6% while group2 abortion rate of 13.3% this was significant. The time interval from put abortion was 8.04 ± 4.280 hours in group1 and 9.62 ± 5.237 hours in group2. Side effects such as diarrhea, nausea and headache showed no statistically significant difference in both patients.